A unique Cretaceous–Paleogene lineage of piranha-jawed pycnodont fishes - Romain Vullo (Nature Portfolio, 2017)
Abstract The extinct group of the Pycnodontiformes is one of the most characteristic components of the Mesozoic and early Cenozoic fish faunas. These ray-finned fishes, which underwent an explosive morphological diversification during the Late Cretaceous, are generally regarded as typical shell-crushers. Here we report unusual cutting-type dentitions from the Paleogene of Morocco which are assigned to a new genus of highly specialized pycnodont fish. This peculiar taxon represents the last member of a new, previously undetected 40-million-year lineage (Serrasalmimidae fam. nov., including two other new genera and Polygyrodus White, 1927) ranging back to the early Late Cretaceous and leading to exclusively carnivorous predatory forms, unique and unexpected among pycnodonts. Our discovery indicates that latest Cretaceous–earliest Paleogene pycnodonts occupied more diverse trophic niches than previously thought, taking advantage of the apparition of new prey types in the changing marine ecosystems of this time interval. The evolutionary sequence of trophic specialization characterizing this new group of pycnodontiforms is strikingly similar to that observed within serrasalmid characiforms, from seed- and fruit-eating pacus to flesh-eating piranhas.